Behavioral impact of disaster education: Evidence from a dance-based program in Indonesia. (May 2020) - Shoji, Masahiro; Takafuji, Yoko; Harada, Tetsuya
Abstract: Despite its potential role in reducing disaster mortality, the rigorous evaluation of the impact of disaster education on children's disaster responses, such as evacuation behavior, is scarce. This study examines the impact of a newly introduced Indonesian program on students' earthquake response. The program is carefully designed based on psychological theories and anecdotal lessons from different countries. It is also easy to understand and cost-effective. Exploiting the fact that the treatment schools for the pilot program were selected based on two observable criteria, we employ the propensity score weighting estimation. The results show positive effects on perception regarding students' ability to cope with disaster risk and likelihood of taking appropriate response during an earthquake. The participants are also more likely to self-learn and have higher knowledge of disaster risks. Furthermore, there exists a significant effect on earthquake response even among students with poor learning attitude at school. This feature is preferable for disaster education in developing countries, as those residing in disaster-vulnerable areas tend to have poor educational background.